Pengaruh Perjodohan Terhadap Pernikahan Anak Yang Mengakibatkan Perceraian (Studi Putusan Pengadilan Agama Stabat Nomor 345/Pdt.G/2023/PA.Stb) - Tiur Ayuningtias Pauliza Putri Lubis; Azhar Azhar; Syahrul Affan (Tabsyir: Jurnal Dakwah dan Sosial Humaniora, 2023)
Arranged marriage is a method of finding a husband/wife partner carried out by a third party, whether parents or others. In this research, it is a case of the influence that occurs as a result of a child being chosen by his parents as a mate which results in divorce. This case was determined by the Stabat Religious Court with case number 345/Pdt.G/2023/PA.Stb. There are two points that are the main focus of this issue, with the aim of finding out the influence of arranged marriages which can result in divorce and then the decision of the Stabat Religious Court regarding divorce due to arranged marriages. This study uses a qualitative method. Data analysis using descriptive methods This type of research is research using a normative legal approach method that examines literature studies, namely research on secondary data. Data collection techniques using interviews and documentation. The conclusion of this research is that the wife's petition for divorce was granted by the panel of judges at the Stabat Religious Court and charged all court costs to the Petitioner.